Implementation of "Judicial Pardon" for Minors Based on the National Criminal Code and SPPA - Dony Setiawan Putra (Jurnal Penelitian, 2025)
Judicial Pardon is a new sentencing guideline contained in the Indonesian National Criminal Code, the existence of Judicial Pardon or the forgiveness of this judge is especially for perpetrators who have indeed committed minor criminal acts, but the regulation is not cumulative where in pardon the judge does not only look at the lightness of the criminal act, but also about the person of the perpetrator and the circumstances at the time the criminal act was committed. Especially in perpetrators (children) based on the UUSPPA prioritizes restorative justice, namely non-formal or out-of-court settlements, but for serious crimes it must be resolved in a formal court, namely through a criminal decision by a judge. The purpose of this study is to describe and solve the legal problems that occur to the perpetrator (children), especially minors and also the process of applying Judicial Pardon for children who commit serious crimes, the formulation of the problem raised first is whether the criminal guidelines regarding ''Judicial Pardon'' can be applied to minors based on the National Criminal Code and UUSPPA, the second is how to settle the law regarding serious crimes committed by minors. The research method used is normative legal research. The results of the first research in the National Criminal Code and UUSPPA have regulated the Judicial Pardon where the National Criminal Code implements the SPPA Law so that it can be applied not only to children but also to adults, related to the application of judge's pardon is indeed specifically for the perpetrator (child), but for the perpetrator (child) who commits a serious criminal act must be punished, They (children) should be given a "Judicial Pardon" halfway or not absolutely, in other words, they are forgiven, but they are still given action regarding the serious crime that has been committed. Second, the legal settlement that occurs to the perpetrator (child) can be done by means of Judicial Pardon considering that the article that regulates Judicial Pardon is not cumulative because there is a comma and or so that if one of them is fulfilled, the Judge can grant a Judicial Pardon One of them is looking at the personal side of the perpetrator (child) where children still have a labile mindset so that they can still be directed to be good and acceptable to the community again.